Sprawowanie sakramentu pokuty i pojednania w świetle prawa kanonicznego i liturgicznego z uwzględnieniem specyfiki warunków polskich - Janczewski, Zbigniew (Prawo Kanoniczne, 2006)
Poland is a country where majority of inhabitants are faithful of Roman Catholic Church. That people relative frequently admit to the sacrament of penance ad reconciliation. Every day the priests be on duty in the confessionals. Particular difficult is to confess a few days before Easter and Christmas. Then near confessionals by all the days are very long queues of penitents. Under such circumstances Decision of Polish Episcopal Conference contained in the Ordo Paenitentiale recommends for example to use rite of reconciliation many penitents with individual confession and absolution. The minister can use also shortening rite of penance, apart from instruction for penitents. This elaboration shows also the situations when is necessary to refuse absolution or set aside absolution for the future.